Tinjauan Yuridis terhadap Mekanisme Kepailitan sebagai Solusi Penyelesaian Utang-Piutang di Indonesia - Kelfin Eka Putra Banu; Richardus Wesly Teka; Claudio Xaverius Oematan; Alexadros Mone; Fransiska Owa Da Santo; Filemon Fridolino Ngebos (Pusat Riset dan Inovasi Nasional, 2025)
Debt-receivable problems are classic problems in economic activities that if not resolved properly can result in legal uncertainty and losses to the parties involved. One of the legal instruments provided in the Indonesian legal system to resolve these disputes is through the bankruptcy mechanism. This study aims to review the legal provisions regarding bankruptcy as regulated in Law Number 37 of 2004 and evaluate the effectiveness of its implementation as a solution to resolving debt-receivable problems. The method used in this study is the normative legal approach, by reviewing statutory provisions, legal doctrine, and court decisions. The results of the study indicate that although normatively the bankruptcy mechanism has a clear legal structure, its implementation in the field still faces obstacles in terms of process efficiency, protection of creditor and debtor rights, and supervision of curators. Therefore, policy updates and optimization of the function of judicial institutions are needed to increase public trust in this mechanism.